Diagnosis of Tuberculosis Following World Health Organization-Recommended Criteria in Severely Malnourished Children Presenting With Pneumonia - Mohammod Jobayer Chisti MBBS, MMed, PhD; Mohammed Abdus Salam MBBS; Abu S. M. S. B. Shahid MBBS; K. M. Shahunja MBBS; Sumon Kumar Das MBBS; Abu Syed Golam Faruque MBBS, MPH; Pradip Kumar Bardhan MBBS, MD; Tahmeed Ahmed MBBS, PhD (SAGE Publishing, 2017)
Evidences on diagnosis of tuberculosis (TB) following the World Health Organization (WHO) criteria in children with severe acute malnutrition (SAM) are lacking. We sought to evaluate the WHO criteria for the diagnosis of TB in such children. In this prospective study, we enrolled SAM children aged <5 with radiological pneumonia. We collected induced sputum and gastric lavage for smear microscopy, mycobacterial culture, and Xpert MTB/RIF. Using the last 2 methods as the gold standard, we determined sensitivity, specificity, and positive and negative predictive values of WHO criteria (n = 388). However, Xpert MTB/RIF was performed on the last 214 children. Compared to mycobacterial culture-confirmed TB, sensitivity and specificity (95% confidence interval) of WHO criteria were 40 (14% to 73%) and 84 (80% to 87%), respectively. Compared to culture- and/or Xpert MTB/RIF-confirmed TB, the values were 22% (9% to 43%) and 83 (79% to 87%), respectively. Thus, the good specificity of the WHO criteria may help minimize overtreatment with anti-TB therapy in SAM children, especially in resource-limited settings.